Alterations of Dopamine-Related Transcripts in A11 Diencephalospinal Pathways after Spinal Cord Injury - Shunyi Zhao; Jaclyn H. DeFinis; Shaoping Hou (Neural Plasticity)
The diencephalic A11 nuclei are the primary source of spinal dopamine (DA). Neurons in this region project to all levels of the spinal cord. Traumatic spinal cord injury (SCI) often interrupts descending and ascending neuronal pathways and further elicits injury-induced neuronal plasticity. However, it is unknown how A11 neurons and projections respond to SCI-induced axotomy. Based on preliminary observation, we hypothesized that A11 DA-ergic neurons rostral to the lesion site might change their capacity to synthesize DA after SCI. Adult rats received a complete spinal cord transection at the 10th thoracic (T10) level. After 3 or 8 weeks, rostral (T5) and caudal (L1) spinal cord tissue was collected to measure mRNA levels of DA-related genes. Meanwhile, A11 neurons in the brain were explicitly isolated by laser capture microdissection, and single-cell qPCR was employed to evaluate mRNA levels in the soma. Histological analysis was conducted to assess the number of A11 DA-ergic neurons. The results showed that, compared to naïve rats, mRNA levels of tyrosine hydroxylase (TH), dopamine decarboxylase (DDC), and D2 receptors in the T5 spinal segment had a transient decrease and subsequent recovery. However, dopamine-β-hydroxylase (DBH), D1 receptors, and DA-associated transcription factors did not change following SCI. Furthermore, axon degeneration below the lesion substantially reduced mRNA levels of TH and D2 in the L1 spinal segment. However, DDC transcript underwent only a temporary decrease. Similar mRNA levels of DA-related enzymes were detected in the A11 neuronal soma between naïve and SCI rats. In addition, immunostaining revealed that the number of A11 DA neurons did not change after SCI, indicating a sustention of capacity to synthesize DA in the neuroplasm. Thus, impaired A11 diencephalospinal pathways following SCI may transiently reduce DA production in the spinal cord rostral to the lesion but not in the brain.